Determinan The Evaluation of Work Unit Application System (Sistem Aplikasi Satker (SAS) : An Information System of Success Model Approach - Laksana, Pandu Krida; Subroto, Bambang; Baridwan, Zaki (Universitas Negeri Malang, 2017)
This study aims at examining and analyzing the effects of system quality, information quality, the significance of system onÂ user satisfaction partaking as mediating variables. The survey was carried through by way of census mode (total sampling) in all individuals using SAS and were employed in work units (Satker) partnering with KPPN Sidoarjo in fiscal year 2016, with the number of 86 research subjects. The used analysis methods was SEM-PLS with the assistance of WarpPLS Software 5.0. The results showed that there was a positive effect of the system quality, the importance of the system, and the usability of the system on usersâ satisfaction, but the information quality was not empirically proven effective on user satisfaction. The system quality and information quality positively effected on the usability of the system, but the importance of the system did not affect the usefulness of the system.Â Keywords: Usability, user satisfaction, information quality, system quality, significance of the system.